Evaluation of Exercise Addiction of Obese Adults - Uysal, Yucel; Toros, Turhan; Cetin, Mehmet Cagri; Korkmaz, Cihat; Serin, Emre; Ozyol, Funda Coskun (Progress in Nutrition, 2022)
Study objectives: The aim of this study was to evaluate exercise addiction levels of adults and search the correlation between exercise addiction and gender, age, and exercise experience. Methods: A total of 148 obese (body mass index > 30) men and women who exercise regularly at least one hour per day and at least three days per week for four months were recruited randomly for the study. Data were collected using "Demographic Information Form" and "Exercise Addiction Scale (EAS)". Results: Scores of EAS were evaluated through these three sub-dimensions of the scale; "Excessive Focus and Emotion Change", "Postponement of Individual-Social Needs and Conflict", "Tolerance Development and Passion". Statistically significant relationships were found between sub-dimension scale scores and gender, age, and exercise experience. In all sub-dimension of EAS scores were higher in women than men. Scores of younger adults were higher than the older group. In addition, it was found that individuals who have exercise experience of more than 5 years had lower addiction scores less experienced group. Conclusion: The results suggest that women, older adults, and less experienced individuals have more tendency for exercise addiction.